Economic Resources, Parenting, and Children's Behavior Problems: An Opportunity for Resilience? - Rohrs, RoseMarie. (Tufts University. Tisch Library., 2022)
Thesis (M.A.)--Tufts University, 2022.; Submitted to the Dept. of Child Development.; Advisor: Ann Easterbrooks.; Committee: Tama Leventhal, and Rebekah Levine Coley.; Keyword: Developmental psychology.